The Effect of Audiolyfe Stimulation on the Optimization of Children's Potential and Talents: A Case Study in Banda Aceh - Fathiyah Ma’ani (Eduvest - Journal of Universal Studies, 2026)
Recognizing and developing children’s potential and talents from an early age plays an important role in shaping their future. However, many children face challenges such as difficulty discovering their interests or lacking enthusiasm to explore their own potential. Proper stimulation, including audio-based technologies such as Audiolyfe, can help address these issues. This study aims to analyze the influence of Audiolyfe stimulation on the development of children’s potential and talents in Banda Aceh. Using quantitative methods and a quasi-experimental approach, this research involved 25 children aged 0–12 years who were selected through purposive sampling techniques. Data were collected through observation and questionnaires, then analyzed using descriptive statistics. The results show that Audiolyfe stimulation has a significant influence on the development of children’s potential and talents. A noticeable difference was observed between the pretest and posttest results, in which children who received regular stimulation demonstrated increased creativity, cognitive abilities, and enthusiasm for learning. These findings indicate that Audiolyfe can be an effective tool to support the optimization of children’s abilities from an early age. Through a structured approach, this technology contributes meaningfully to preparing a younger generation that is more confident and better equipped with the skills needed to face future challenges.